THU0239 Drug Survival and Clinical Efficacy of 7 Years Etanercept Treatment in Patients with Ankylosing Spondylitis: Results from the Glas Cohort. (9th June 2015) - Arends, S.; Brouwer, E.; Wink, F.; Bos, R.; Maas, F.; Bootsma, H.; van der Veer, E.; Spoorenberg, A.
Abstract : Background: Randomized controlled trials and open-label extension studies have demonstrated the clinical efficacy and safety of tumor necrosis factor-alpha (TNF-α) blocking therapy in patients with ankylosing spondylitis (AS). Objectives: The aim of the present study was to investigate the 7-year drug survival and long-term efficacy regarding disease activity, physical function and quality of life in AS patients treated with etanercept in daily clinical practice. Methods: All consecutive AS patients from the prospective observational Groningen Leeuwarden AS (GLAS) cohort who started etanercept because of active disease between November 2004 and December 2006 were included in the analyses. Patients were evaluated during 7 years according to a fixed protocol with assessments of disease activity, physical function, and quality of life. Continuation of treatment was based on BASDAI improvement of at least 2 units and/or expert opinion. Results: Of the 67 included patients, 72% were male, mean age was 41 years (SD ±9), median duration of symptoms 16 years (range 2-41), and 86% were HLA-B27+. In total, 36 of the 67 (54%) patients were still using etanercept after 7 years. Almost half (n=14) of the 31 patients who discontinued etanercept stopped within the first year of follow-up. The remaining patients (n=17) stopped spread in the next 6 years. Reasons for treatment discontinuation were adverse events (n=17), inefficacy (n=9), pregnancy wish (n=2), or lost to follow-up (n=3). Etanercept treatment resulted in a rapid (after 6 weeks) and sustained improvement in BASDAI, ASDAS, CRP, physician GDA, spinal mobility, BASFI, and ASQoL during 7 years of follow-up (Table 1 ). After 7 years, low disease activity based on BASDAI<4, ASDAS<2.1, and CRP<5 was present in 72%, 70%, and 68% of the 36 patients, respectively. All patients had low disease activity according to the physician (NRS <4). Inactive disease based on ASDAS<1.3 was observed in 36%, and ASAS partial remission in 29% of the patients. Conclusions: This study in daily clinical practice confirms the long-term clinical efficacy of etanercept treatment in AS patients who started this treatment because of active disease. Approximately half of these patients showed long-term improvement in disease activity, physical function, and quality of life during the 7 years of follow-up. Acknowledgements: The GLAS cohort was supported by an unrestricted grant from Pfizer. Pfizer had no role in the design, conduct, interpretation, or publication of this study. Disclosure of Interest: S. Arends Grant/research support from: Abbott, Pfizer, Wyeth, E. Brouwer Grant/research support from: Abbott, Pfizer, Wyeth, F. Wink: None declared, R. Bos: None declared, F. Maas: None declared, H. Bootsma: None declared, E. van der Veer: None declared, A. Spoorenberg Grant/research support from: Abbott, Pfizer, Wyeth, Consultant for: Abbvie, Pfizer, UCB